2015
DOI: 10.1182/blood-2014-09-570192
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of hematopoietic stem cell niches

Abstract: The hematopoietic stem cell (HSC) niche commonly refers to the pairing of hematopoietic and mesenchymal cell populations that regulate HSC self-renewal, differentiation, and proliferation. Anatomic localization of the niche is a dynamic unit from the developmental stage that allows proliferating HSCs to expand before they reach the bone marrow where they adopt a quiescent phenotype that protects their integrity and functions. Recent studies have sought to clarify the complexity behind the HSC niche by assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
259
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(265 citation statements)
references
References 106 publications
(113 reference statements)
2
259
0
4
Order By: Relevance
“…Conversely, Dicer1 knockout cells exhibited a reduction in JAG1 expression (GDS3404 and GDS4504). These findings suggest that osteoblasts and MSCs play different roles in supporting normal hematopoiesis, 37 and JAG1 expression could be regulated by β-catenin signaling and miRNA biogenesis. Consistent with these previous reports, we and others reported that mRNA expression of hematopoietic factors in MDS-derived MSCs was significantly disturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Dicer1 knockout cells exhibited a reduction in JAG1 expression (GDS3404 and GDS4504). These findings suggest that osteoblasts and MSCs play different roles in supporting normal hematopoiesis, 37 and JAG1 expression could be regulated by β-catenin signaling and miRNA biogenesis. Consistent with these previous reports, we and others reported that mRNA expression of hematopoietic factors in MDS-derived MSCs was significantly disturbed.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The clinical observations that bone metastases from solid tumors from infancy to adulthood concord with the centripetal migration of hematopoiesis with aging suggest that bone metastases require subversion of the haematopoietic niche. Although endosteal, perivascular and other locations of the haematopoietic niche continue to be assessed, 4 mesenchymal stromal cells and their osteoblastic derivatives have been previously implicated as architects of the haematopoietic niche. [5][6][7] In experimental murine models prostate cancer cells can be demonstrated to compete with CD45C haematopoietic stem cells for a niche specified by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…HSCs [8,59,69,70]. However, other reports suggest that osteoblasts had no impact on primitive HSCs, but on committed B lymphocyte progenitors [71,72].…”
Section: Discussionmentioning
confidence: 78%